Perdagangan Bebas di Era Digital : Dilema Ekonomi Indonesia - Ivana Nabila Putri; Pascal Kharua Albari; Jessenia Kayla Putri; Mohamad Zein Saleh (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
Free trade in the digital era opens up export opportunities while increasing competition for imported products in the domestic market, which has the potential to weaken local industries. This research highlights the importance of strategic policies, such as MSME incentives and strengthening digital capacity, to increase the competitiveness of local products. The SWOT approach points to digital transformation opportunities and the need for cross-sector collaboration to drive innovation and sustainable economic growth.